2017
DOI: 10.1073/pnas.1613165114
|View full text |Cite
|
Sign up to set email alerts
|

Distinct C- mannosylation of netrin receptor thrombospondin type 1 repeats by mammalian DPY19L1 and DPY19L3

Abstract: Thrombospondin type 1 repeats (TSRs) occur in diverse proteins involved in adhesion and signaling. The two extracellular TSRs of the netrin receptor UNC5A contain WxxWxxWxxC motifs that can be C-mannosylated on all tryptophans. A single C-mannosyltransferase , modifying the first two tryptophans, occurs in Caenorhabditis elegans, but four putative enzymes (DPY-19-like 1-4, DPY19L1-4) exist in mammals. Single and triple CRISPR-Cas9 knockouts of the three homologs that are expressed in Chinese hamster ovary cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(100 citation statements)
references
References 42 publications
4
88
0
1
Order By: Relevance
“…5C), but it is unclear whether this affects C-␣ManT activity. The fitness score (Ϫ2.4) indicates importance for growth, potentially related to quality control of secretion of the proteins carrying TSRs, and possibly in concert with Glc-Fuc-modifications (69). Because there is no method known to release C-Man, monitoring the outcome will depend on glycopeptide analyses beyond the scope of this project.…”
Section: Other Glycogenes Associated With the Secretory Pathwaymentioning
confidence: 99%
“…5C), but it is unclear whether this affects C-␣ManT activity. The fitness score (Ϫ2.4) indicates importance for growth, potentially related to quality control of secretion of the proteins carrying TSRs, and possibly in concert with Glc-Fuc-modifications (69). Because there is no method known to release C-Man, monitoring the outcome will depend on glycopeptide analyses beyond the scope of this project.…”
Section: Other Glycogenes Associated With the Secretory Pathwaymentioning
confidence: 99%
“…TSRs glycosylation is carried out in the endoplasmic reticulum (22,26), and in studies performed in mammalian cell and Caenorhabditis elegans, defects in both C-mannosylation and O-fucosylation have been shown to affect protein stabilization and secretion, albeit with protein-to-protein variability (19,23,(27)(28)(29)(30)(31). A knockout of pofut2 is embryonically lethal in mice (31).…”
mentioning
confidence: 99%
“…Moreover, Shcherbakova et al . demonstrated that murine DPY19L1 and DPY19L3 are C ‐mannosyltransferases of the netrin receptor UNC5A .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we first reported human DPY19L3 to be a C-mannosyltransferase of R-spondin1 (Rspo1), which harbors the C-mannosylation consensus sequence-Trp 156 -Gly-Pro-Cys-in its TSR [13]. Moreover, Shcherbakova et al demonstrated that murine DPY19L1 and DPY19L3 are C-mannosyltransferases of the netrin receptor UNC5A [14].…”
Section: Introductionmentioning
confidence: 99%